2016
DOI: 10.3233/dev-160185
|View full text |Cite
|
Sign up to set email alerts
|

On Being in the Wrong Place: The Role of Children’s Conceptual Understanding and Ballgame Experience when Judging a Football Player’s Offside Position

Abstract: We investigated the role of children’s conceptual understanding and ballgame experience when judging whether a football player is in an offside position, or not. In the offside position, a player takes advantage of being behind the defence line of the opposing team and just waits for the ball to arrive in order to score a goal. We explained the offside rule to 7- and 9-year-old children with a Subbuteo setup. They produced drawings of an offside position until it was correct (drawing to criterion). Thereafter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…One conclusion from these studies is that sex differences in small samples are dependent on the interest of the particular participants in the samples. Girls with little interest in football are not as good as boys in identifying an offside position [52]. Boys who are interested in pen and paper are also good in reading [59].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One conclusion from these studies is that sex differences in small samples are dependent on the interest of the particular participants in the samples. Girls with little interest in football are not as good as boys in identifying an offside position [52]. Boys who are interested in pen and paper are also good in reading [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, also spatial memory which is supposed to depend on spatial concepts can be learned by repetition without the necessity of spatial strategies [46] as long as objects and places stay the same in repeated viewings. Moreover, the study on the understanding of the offside rule [52] showed that while the LC-operator was allowing boys to excel in the visual identification task of the wrong place, this did not prevent systematic judgement. In drawings, the LC-operator in combination with the F-operator would allow boys to avoid proliferation of detail so that the transition to viewpoint perspective and visual realism would involve just a small adjustment of contour [30,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations